VISUAL AIDS IN ENHANCING THE LEARNING PROCESS IN ENGLISH LANGUAGE IN A PRIVATE SCHOOL (AKHMAD EDUCATION) - Numonova, Mukharramkhon (QO‘QON UNIVERSITETI XABARNOMASI, 2024)
There has been a growing awareness of the importance of the use of various teaching aids to support the learning process especially in teaching of English as a second language. These aids play a vital role in achievement of various needs of learners with different learning style. This paper aims at assessing the effectiveness of images, charts, and multimedia in enhancing the learning process of English to learners. The study assumes that visuals help enhance understanding significantly, improve recall of concepts in a given language and enhance students’ interest. The research explores various types of learning environments in terms of classroom practices, using survey answers of participants and academic performance in association with visual aids. The research indeed indicates that visual support improves comprehension of intricate syntactic patterns and increased recognition of new words. They also encourage class discussions and class activities as well as ensuring that every student is included in the classroom learning process. The implications of the study show that integrating use of visual aids is critical in enhancing the effectiveness of teaching English.